At the frontier of epigenetics of brain sex differences - McCarthy, Margaret M.; Nugent, Bridget M. (Frontiers in Behavioral Neuroscience, 2015)
The notion that epigenetics may play an important role in the establishment and maintenance of sex differences in the brain has garnered great enthusiasm but the reality in terms of actual advances have been slow. Two general approaches include the comparison of a particular epigenetic mark in males versus females and the inhibition of key epigenetic enzymes or co-factors to determine if this eliminates a particular sex difference in brain or behavior. The majority of emphasis has been on candidate genes such as steroid receptors. Only recently have more generalized survey type approaches been achieved and these promise to open new vista’s and accelerate discovery of important roles for DNA methylation, histone modification and microRNAs. Technical challenges abound and while not unique to this field will require novel thinking and new approaches by behavioral neuroendocrinogists.